Regulasi dan Implementasi Fintech Syariah dalam Mendukung Inklusi Keuangan Berbasis Prinsip Syariah - Yusuf Karim (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2025)
Sharia fintech as a financial technology innovation based on sharia principles is growing rapidly and becoming a financial inclusion solution that reaches the wider community, especially those who want sharia-compliant financial products. However, the development of sharia fintech requires adaptive regulations so that its implementation does not conflict with the principles of sharia economic law and is able to provide protection for consumers. This study aims to examine the regulations governing sharia fintech in Indonesia and how they are implemented in supporting sharia-compliant financial inclusion. The method used is a qualitative study with analysis of regulatory documents and interviews with sharia fintech industry players and regulators. The results of the study revealed that sharia fintech regulations are currently still in the development stage and require synchronization between financial authorities and sharia supervisory institutions. On the other hand, sharia fintech has been able to expand financial access for people who were previously unreached by conventional banking. However, there are challenges in ensuring that all transactions are in accordance with sharia principles and consumer data protection. This study recommends strengthening the regulatory framework that accommodates the dynamics of technology and sharia principles in a balanced manner and increasing education for the community and fintech business actors. Thus, sharia fintech can be an effective instrument in encouraging inclusive and sustainable economic development in accordance with Islamic values.